Effect of Soaking Duration Bulb in 75% Old Coconut Water on Growth and Yield of Bima Brebes Shallot (Allium cepa L.): Plant Height, Leaf Count, Bulb Number, Bulb Diameter, and Bulb Weight - Muhammad Robiyansyah; Nanik Lestariningsih; Lilin Ika Nur Indah Sari (Science Education and Application Journal, 2025)
Effect of Soaking Duration Bulb in 75% Old Coconut Water on Growth and Yield of Bima Brebes Shallot (Allium cepa L.): Plant Height, Leaf Count, Bulb Number, Bulb Diameter, and Bulb Weight. Shallot production in Central Kalimantan in 2021 decreased from the previous year due to the lack of application of growth regulators by farmers in addition to fertilizing. The provision of growth regulators from coconut water is one effort to increase crop production. Coconut water contains minerals and growth hormones that are very much needed by plants. Similar research has been conducted previously with 75% young coconut water, but the administration with old coconut water has not been carried out, so it becomes the basis for the research. This study aims to determine the effect of the duration of soaking shallot bulbs of the Bima Brebes variety in 75% old coconut water on the growth and yield of bulbs. The study was conducted in July-October 2023, located in Menteng Village, Palangka Raya City. This study used a 75% concentration of old coconut water with 5 different treatment levels based on a completely randomized design method with 8 replications. Observations and data collection included plant height, number of leaves, number of bulbs, bulb diameter, and wet weight of bulbs. The data obtained were analyzed using Analysis of Variance (ANOVA) and Least Significant Difference (LSD) with the help of SPSS software. The results of the ANOVA and LSD tests showed that soaking shallot bulbs in old coconut water had a significant effect on the number of bulbs (p value = 0.02 <0.05) with P2 = 10.13 and bulb weight (p value = 0.02 <0.05) with P2 = 8.10 g. The results of the analysis of plant height, number of leaves, and bulb diameter had no effect. Soaking shallot bulbs in old coconut water for 4 hours was quite optimal in increasing the number of bulbs and wet weight of bulbs compared to other treatments. Soaking the bulbs for 4 hours was able to increase the number of bulbs by 131% and the weight of bulbs by 169% so that these findings can be applied by shallot farmers in increasing bulb yields. The success rate of this study was greatly influenced by factors and constraints such as high humidity and low sunlight intensity, which can affect bulb development